A dish-stirling solar concentrator coupled to a seasonal thermal energy storage system in the southern mediterranean basin: A cogenerative layout hypothesis. (15th October 2020) - Guarino, Stefania; Buscemi, Alessandro; Ciulla, Giuseppina; Bonomolo, Marina; Lo Brano, Valerio
Highlights: Layout for a dish-Stirling coupled to a geothermal storage system presented. Energy performance of the cogenerative solar concentrator presented. Influence of several physical parameters investigated to optimise the system. Identification of a incentivisation policy for a cogenerative dish-Stirling plant. Evaluation of energy and economic viability of the cogenerative layout. Abstract: In the future, renewable energy sources will increasingly represent an efficient energy source capable of meeting the demands of residential and industrial buildings avoiding the emissions of greenhouse gases into the atmosphere. In this paper, a heat and electric power cogeneration plant implementing a field of dish-Stirling collectors, a seasonal geothermal storage and a system of water-to-water heat pumps is proposed for the first time. The cogeneration plant has been designed both to supply thermal energy to the heating system of Building 9 of the Department of Engineering in Palermo and to produce electricity. The operation of the plant has been tested by means of hourly-based numerical simulations that have been carried out using a numerical model implemented with Transient System Simulation Tool. The experimental data of a pilot dish-Stirling collector, located in the same area, has been used to carefully calibrate the numerical model. Using energy and economic performance indicators, it was possible to select the best configurations among 1440 analysed cases. Results of simulations show that with the best plant configuration, it is possible to cover 97% of the building's annual thermal loads with energy produced by the solar system. The remaining 64% of electrical energy produced by the electric engines is free to be used for other applications. Financial analyses have shown that market penetration of this type of plant would need a strong support through incentives.